Efeitos do bloqueio da síntese de corticosterona nos testes de labirinto em cruz elevado e campo aberto em machos e fêmeas em diferentes fases do ciclo estral - Busnardo, Pedro Henrique Timossi (Universidade Federal de São Carlos, 2025)
Corticosterone is a glucocorticoid hormone involved in fear and anxiety responses in threatening situations. The inhibition of its synthesis using metyrapone has been shown to reduce unconditioned defensive responses in male rats. Recent studies suggest that females may exhibit different responses from males depending on their estrous cycle phase. This study aimed to expand the understanding of corticosterone's role in unconditioned fear expression in males and females at different estrous cycle phases. A total of 111 adult Wistar rats (73 females and 38 males) were used. Fourteen days before testing, animals were habituated to the laboratory, and female estrous cycle phases were determined daily. On the test day, females were grouped into proestrus/estrus or metestrus/diestrus according to their current cycle phase. Control animals received an intraperitoneal vehicle injection, while experimental groups received metyrapone at doses of 30 or 60 mg/kg. Twenty minutes post-administration, animals underwent 5-minute behavioral assessment in the elevated plus maze (EPM), followed by 5 minutes in the open field test (OFT) after a 10-minute interval. In the EPM, metyrapone decreased rearing and increased open-arm entries in males compared to controls. In females, regardless of cycle phase, metyrapone reduced closed-arm entries and rearing. In the OFT, metyrapone increased center time and crossings in males. In proestrus/estrus females, it increased center time and peripheral crossings while reducing immobility. In metestrus/diestrus females, it increased center time but decreased rearing and immobility. These findings indicate a reduction in defensive responses in both tests, suggesting a clear anti-aversive effect. However, metyrapone also influenced overall exploratory behavior, highlighting its broader impact on locomotion and anxiety-like responses.
Effects of corticosterone synthesis inhibition in the elevated plus maze and open field tests in males and females at different estrous cycle phases
Keywords: Medo incondicionado; Metirapona; Eixo hipotálamo-pituitária-adrenal; CIENCIAS HUMANAS::PSICOLOGIA